2010
DOI: 10.3171/2010.3.focus1058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arthroplasty design on cervical spine kinematics: analysis of the Bryan Disc, ProDisc-C, and Synergy Disc

Abstract: Object Cervical total disc replacement has emerged as a surgical option to preserve motion and potentially avoid adjacent-segment disease after anterior cervical discectomy and fusion. Recently, much attention has been directed at the ability of a given device to maintain and/or restore normal segmental alignment. Nonphysiological disc and segmental angulation could result in increased stresses transmitted to the facet joints and posterior elements, conflicting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 47 publications
0
31
0
3
Order By: Relevance
“…43 Three devices were included in that study: Bryan Cervical Disc, ProDisc-C (DePuy Synthes, Inc.), and Synergy Cervical Disc (Synergy Disc Replacement, Inc.). The study was concerned primarily with characteristics at the index level, analyzing postoperative range of motion, disc height, sagittal plane translation, angulation, and center of rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Three devices were included in that study: Bryan Cervical Disc, ProDisc-C (DePuy Synthes, Inc.), and Synergy Cervical Disc (Synergy Disc Replacement, Inc.). The study was concerned primarily with characteristics at the index level, analyzing postoperative range of motion, disc height, sagittal plane translation, angulation, and center of rotation.…”
Section: Discussionmentioning
confidence: 99%
“…34,36,58 One potential reason for the discrepancy in findings between previous studies may be due to the techniques used. Previous studies investigating cervical spine motion are often limited to a 2D analysis 18,34,39,43,45,53 or cadaveric simulations. 14,59 Although cadaveric simulations are ideal for measuring 3D motion patterns, they are not designed to reproduce the joint forces, muscle forces, and complex motion patterns associated with in vivo conditions.…”
mentioning
confidence: 99%
“…Tem-se observado resultados semelhantes com essas próteses em curto prazo (dois anos de seguimento) 24,26 .…”
Section: Resultsunclassified
“…Na prática a artroplastia foi tão eficaz quanto a artrodese 26 . Na nossa casuística tivemos um único caso de mielopatia e a recuperação foi satisfatória com a artroplastia.…”
Section: Pré-operatóriounclassified
“…In a retrospective cohort of 259 patients, neck pain was more common in the arthroplasty group at 15.8% (n=27 patients) when compared to the fusion group at 12.5% (n=11 patients) [21]. Although some authors have suggested that ball and socket can provide a modest increase in alignment, Rabin et al demonstrated that a lordotic configuration of ProDisc-C endplates was associated with restricted motion from neutral to extension [5,[22][23][24]. Similarly, Du et al described that even with a ball and socket design that incorporated 7˚ of lordosis in endplates (Discover Cervical Disc, DePuy Spine, Raynham MA, USA), there were reported cases of device endplate kyphosis [25].…”
Section: Discussionmentioning
confidence: 99%